KEMAMPUAN TANAMAN GLODOGAN Polyalthia longifolia SONN. SEBAGAI PENEDUH JALAN DALAM MENGAKUMULASI Pb UDARA BERDASARKAN RESPON ANATOMIS DAUN DI PURWOKERTO - Rizqi Dwi Ardyanto; Slamet Santoso; Siti Samiyarsih (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Polyalthia longifolia is a plant that used as a roadside in Purwokerto. This study aimed to determine the ability of the plant P. longifolia in the air and accumulate Pb anatomic response to the Pb concentration in the leaves of P. longifolia. The methods of research used survey methods. Roadside plant leaf samples were taken by purposived sampling at six locationsmain street in Purwokerto, there are Jenderal Soedirman, Dr. Soeparno, HR. Bunyamin, Commisioner Bambang Soeprapto and Gerilya. The independent variable was the ambient air Pb and Pb leaf was the dependent variable. The main parameters investigated were air Pb concentrations, Pb leaves, stomata anatomical characters and thick mesophyll tissue. Parameter support was the traffic density. The results showed that the highest concentration of Pb in the air with a concentration of 0.1020 μg/m3 per hour on Gerilya street and the lowest in DR. Soeparno street with concentrations of 0.0048 μg/m3 per hour, it can be concluded that an ambient air Pb in six study sites are still under ambient air quality in Central Java, which is 2 μg/m3 per 24 hours. Leaf Pb concentration was highest in HR. Bunyamin street with a concentration of 0.4980 ± 0.004 ppm and lows in the DR. Soeparno street with concentrations of 0.2786 ± 0.008 ppm. Pb accumulated in leaves affects the density, length, and width of stomata and mesophyll tissue thickness P. longifolia. Pb concentrations was not correlate with the leaf Pb concentration P. longifolia. Pb concentrations of leaves of P. longifolia is closely linked with decreasing density of stomata and mesophyll tissue thickness but not related to the length and width of the stomata.